Salivary Acetylcholine Concentration and Dementia: A Comparative Study in Dhaka City of Bangladesh - Kabir, Md Asiul; Islam, Tahnik Bintay; Akhiruzzaman, -; Ferdous, Samira; Parveen, Mukta; Sarker, Fatema; Sadat, Md Nazmus (Journal of Rangpur Medical College, 2023)
Introduction: Dementia is rapidly becoming a major public health problem worldwide . In dementia, the rate of acetylcholine deficiency is very high. Therefore, it can be assumed that acetylcholine levels may play a potential role in the pathogenesis of dementia. Objective: To evaluate the relationship of salivary acetylcholine concentration with the events of dementia. Methods: This comparative cross-sectional study was carried out during the period of July 2014 to June 2015. Among the purposively selected 120 respondents, 60 respondents were suffering from dementia were selected from the Bangladesh Institute of Research and Rehabilitation for Diabetes, Endocrine and Metabolic Disorder (BIRDEM), National Institute of Neuroscience (NINS), and the Dementia Care Project of Sir William Beveridge Foundation, and the rest 60 were without dementia selected as the comparison group. Results: Out of all study subjects, the mean (±SD) age of dementia patients was 73.10(±4.93) years with an age range of 62 to 84 years and that of in comparative group was 71.20(±5.89) years with an age range of 64 to 85 years. Male (60.0%) was predominant in dementia patients. The mean (±SD) value of Salivary acetylcholine in the dementia group was found 153.93(±98.04) pg/ml and that of in comparative group was 411.50(±112.50) pg/ml. Here Salivary acetylcholine was found lower in dementia patients than comparative group (p<0.001) Conclusion: Salivary acetylcholine level can help to diagnose the risk of development of early dementia. J Rang Med Col. September 2023; Vol. 8, No. 2: 3-6